ESTIMATION OF ANTIHYPERTENSIVE EFFECT EQUABILITY FOR TWO PRESENTATIONS OF NIFEDIPINE WITH DAILY BLOOD PRESSURE MONITORING - V. M. Gorbunov; E. V. Alimova; A. D. Deev (Рациональная фармакотерапия в кардиологии)
Aim. To compare information value of antihypertensive effect equability parameters for two drug formulations of nifedipine: long-acting one (nifedipine-XL) and short-acting one (nifedipine-sa).Material and methods. 147 patients with arterial hypertension (age 53,8±12,5 years) were included into multicenter, cross over design study. Duration of wash-out period was 2 weeks; duration of each treatment course – 4 weeks; interval between courses – 1 week. The following doses of drugs were used: nifedipine-XL – 30-60 mg once daily, nifedipine-sa – 10-20 mg three times a day. Daily blood pressure monitoring (DBPM – Schiller BR-102) was made initially, at the end of each treatment course and at the end of interval between courses. To assess the equability of drug antihypertensive effect “smoothness index” (SI) and coefficient trough effect/peak effect were used (COTP). Information value of these indexes (treatment vs. initial) was assessed by the logical regress analysis.Results. Nifedipine-XL and nifedipine-sa had significant antihypertensive effect according to DBPM data and clinical measurements. Equability of both drugs was similar. χ2 Wald range was 14,7-18,7 (p<0,0001) for SI and 12,7-22,8 for COTP (p<0,001-0,0001).Conclusion. Similar information value of SI and COTP can be explained by the homogeneity of studied patients. Usage both of these indexes for estimation of antihypertensive effect equability is connected with same methodical limits.